Análisis semiótico de la vestimenta del chagra, en el imaginario social de los habitantes del cantón Mocha, periodo enero – julio 2017 - Andagoyes Ramos, Mercy Patricia (2019)
This research work called “Semiotic analysis of the clothing of the Chagra, in the social imaginary of the inhabitants of the Mocha canton, period January- July 2017”, begins with the revaluation of the Ecuadorian Culture through the identification and semiotic analysis of Chagra`s clothing, based on concepts and definitions of communication, theories, semiotics, social imaginaries, cultural identity among others. This project was carried out; with a population and sample established in 378 inhabitants, the techniques and instruments applied for the data collection were surveys and interviews with whose data the analysis and interpretation was carried out, the discussion of results that in the end allowed to raise conclusions and recommendations. This investigation determined that the Chagras stand out and have a greater presence, in the walks and rodeos of the towns of the Ecuadorian mountains, in this way this social group seeks to maintain and preserve their parties, customs and traditions that have become part of the cultural identity of Mocha and is within the social imaginary of its residents, as a culmination of this project was an audiovisual product, to make known the meaning of each of the garments to dress up the Chagra and enhance their participation in the festivities in honor of the patron San Juan Bautista de Mocha that takes place year after year.